AHLI WARIS PENGGANTI DALAM KHI PASAL 185: INOVASI HUKUM YANG BERTENTANGAN DENGAN PRINSIP HIJAB DAN HUKUM ISLAM (Studi Analisis Putusan Mahkamah Agung Nomor 26/Pst.G/2014/PA.JS) - Muhammad Haula Fiqri; Sabilul Muhtadin (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study examines the position of substitute heirs (ahli waris pengganti) under Article 185 of the Compilation of Islamic Law (KHI) concerning inheritance rights for grandchildren, focusing on its compliance with Islamic legal sources. The objectives are: (1) to analyze Supreme Court Decision No. 190 K/Ag/2016 on grandchildren’s inheritance, and (2) to evaluate grandchildren’s legal status in Islamic inheritance law. Using a normative juridical method with statutory (KHI) and case approaches, data was drawn from primary sources (Quran, hadith), secondary sources (classical fiqh texts, journals), and court rulings. Findings reveal that the substitute heir concept contradicts classical fiqh principles: (a) absence in Quran/hadith texts, (b) violation of hijab (exclusion) mechanisms as grandchildren are barred by the deceased’s children, and (c) incompatibility with scholarly consensus (ijma’) of major madhhabs. The study proposes obligatory bequest (wasiat wajibah, max. 1/3 of estate) referring to the Hanafi school as a Sharīʿah-compliant solution to ensure justice while preserving fixed inheritance shares (faraid).